2011
DOI: 10.1097/iae.0b013e31820840ef
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Delayed Vitrectomy in Open-Globe Injuries in Young Patients

Abstract: This consecutive case series underlines the fact that a delayed approach is compatible with good visual prognosis in relatively young patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…Conversely, the later the vitrectomy, the higher the incidence and severity of postoperative complications, mainly PVR [22, 23]. However, other authors investigated longer time [24] (mean 49 days) and they concluded that a delayed approach is compatible with good visual prognosis in relatively young patients.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the later the vitrectomy, the higher the incidence and severity of postoperative complications, mainly PVR [22, 23]. However, other authors investigated longer time [24] (mean 49 days) and they concluded that a delayed approach is compatible with good visual prognosis in relatively young patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sadly, it is still rather common to have the vitrectomy deferred past 2 weeks (very late) [14], even though the disadvantages of such an approach have long been proven [15,16]. Apart from the patient's general condition or other, unavoidable logistical circumstances [17], this long delay is very difficult to justify: it brings hardly any benefit while substantially increasing the incidence and severity of postoperative scarring (PVR, ciliary body destruction and consequent phthisis).…”
Section: Open-globe Traumamentioning
confidence: 99%
“…12 Proper timing of vitrectomy is very important in functional and anatomic prognosis but the benefits of early versus delayed vitrectomy remain controversial. 4,25 The common suggestion is to operate on 10-14 days after OGI, waiting for restoration and PVD, along with avoiding proliferation at same time. Risk of acute inflammatory response and damageassociated hemorrhage could also be reduced during these 2 weeks.…”
Section: Discussionmentioning
confidence: 99%